Water Wise Native Plants for Intermountain Landscapes - Mee, Wendy (University Press of Colorado, 2003)
Today, native plants and water conservation are subjects of vital interest to cities, offices, homeowners, and agriculture alike, as all are affected by the growing shortage of water in the Intermountain region. This comprehensive volume provides specific information about shrubs, trees, grasses, forbs, and cacti that are native to most states in the Intermountain West, and that can be used in landscaping to conserve water, reflect and preserve the region's landscape character, and help protect its ecological integrity. The book is an invaluable guide for the professional landscaper, horticulturist, and others in the Intermountain nursery industry, as well as for the student, general reader, gardener, and homeowner. Water Wise is both convenient and comprehensive. The heart of the book presents hundreds of species, devoting a full page to each, with a description of appearance, habitat, landscape use, and other comments. Color photographs illustrate each plant described. A reader-friendly introduction provides important background on the ecology of the Intermountain West, along with full descriptions of native plant habitats and associations. An accessible resource of accurate native plant information for all readers, Water Wise will be indispensable to professional landscapers and amateurs alike.